Contemporary logistics / Paul Regis Murphy; August Michael Knemeyer - Murphy, Paul Regis
A market-leading text, Contemporary Logistics eplores modern logistics from a managerial perspective. These are characterised by geopolitical tensions in parts of the world, steadily increasing trade, supply chain vulnerabilities caused by severe natural disasters, and an unabated pace of technological advancement. In it, readers see theory come to life through timely, practical, and eciting coverage of logistics fundamentals, and challenges and opportunities for logistics managers in today's dynamic global landscape. This edition provides the most up-to-date insights and perspectives sourced from reviewers, adopters, and other stakeholders.